Baikal seal (Pusa sibirica Gmelin 1788, Phocidae). 2. On the problem of population abundance and its regulation through resumption of commercial hunting - E. A. Petrov (Известия ТИНРО)
Prospects of resumption the Baikal seal (Pusa sibirica) commercial hunting are discussed. Inconsistency of the materials annually submitted by BaikalNIRO for the State report «On the state of Lake Baikal and measures for its protection» for making important decisions regarding the population of Baikal seal is shown. Studies on the population dynamics and methods of its assessment are considered critically, the problems in monitoring of the population are revealed. Adequacy of the presented data on the seals abundance to their real number is doubtful. Current state of the population is considered as quite prosperous, its abundance is high but not excessive. Carrying capacity of the habitat is a variable and difficult to determine, its dynamics is vague and cannot be considered as a reliable basis for resuming the commercial hunting. Groundlessness of such proposals is substantiated and possible negative consequences are shown.